(untitled) (Heteroglossia – studia kulturoznawczo-filologiczne, 2023)
The aim of this paper is to present a new object of linguistic research, namely the entirety of publishing activities (mainly textbooks) intended for the Polish minority living in the USSR. This paper is divided into two parts. In the first section, the author shows the historic and political kontext of this publishing activity for Polish citizen speaking Polish in the interwar period. Thanks to autonomy, there appeared the possibility of education in Polish and publishing of textbooks for the Polish education, which was a part of the Soviet Union’s schooling system – the most important tools for the indoctrination and sovietisation of all nationalities, including the Polish minority. The second part presents the textbook entitled Elementarz by Balk and Charszewska, published in Moscow in 1940 and intended for learning Polish to children starting primary school education. The paper focused on the description of how propaganda and ideology were implemented in the Polish-language textbooks (eg. portraits of Stalin, Lenin, short readings contained difficult, clearly political context for young children). In the second part some distinctive features in the field of syntax, inflexion and lexis found in Elementarz are also presented. Analysis shows that deviations from the general Polish are not numerous (only 12 items). Most of them represents sovietisms – lexems denoting new objects and phenomena of Soviet reality, mainly borrowed from Russian (eg. kołchoz, szturmowo).